The Effect of Communication, work Motivation and Leadership on Employee Performance at PT. Alfa Scorpii Medan - Jeffry Julian Tandela; Fenny Krisna Marpaung (Jurnal Mantik, 2021)
The purpose of this study was to test and analyze the influence of communication, work for motivation, and leadership on employee performance at PT. Alfa Scorpii Medan. This research is descriptive research. The population of this study was employees of PT. Alfa Scorpii Medan Indonesia, totaling 136 people. The sample in this study was 102 people with the Slovin Formula and the Sampling Technique, namely Simple Random Sampling. The statistical method used is multiple linear regression analysis. The results showed that partially stated that Communication, Work Motivation, and Leadership had a significant effect on Employee Performance at PT. Alfa Scorpii Medan. And also simultaneously stated that Communication, Work Motivation, and Leadership have a significant effect on Employee Performance at PT. Alfa Scorpii Medan. The conclusion of this research is simultaneous and partial communication, work motivation, and leadership has a significant effect on employee performance at PT. Alfa Scorpii Medan..